The Maintenance of Bahasa Simalungun in Kecamatan Gunung Maligas - Enni Erawati Saragih; Amrin Saragih; Sri Minda Murni (LINGUISTIK TERAPAN, 2014)
The objective of this study is to identify levels of language endangerment of BahasaSimalungun (BS), to ascertain the domains which are needed proportionally to be managed by the speakers to maintain and to ascertain the ways can be done by the BSS in maintaining BS. This study was based on qualitative approach. Interviews and questionnaire are used as instrument of data. The data were collected by interviewing 22 Simalungunese comprising of second and first generation. The data were analyzed with reference to the theory six levels of language endangerment by UNESCO and Language Use domain by Fishman.The findings showed (1) BS is in the stage of risk up to nearly extinct, this was caused by intermarriage, residence in non Simalungun family and parent attitudes,(2) BS needs to be proportionally managed because most of them are shy to learn and use BS in their daily life, and (3) 20 options offered to maintain BS and18 options were agreed by using BS in wedding ceremony (family domain), using BS in IKEIS (friendship domain), using BS in Perwiritan (religion domain), learn BS as Mulok (educational domain), and using BS in selling and buying activity (employment domain). Key words: Language maintenance; Language endangerment.